2010
DOI: 10.1049/iet-rpg.2009.0205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterisation of flow effects on marine current turbine behaviour and on its wake properties

Abstract: Experimental results of tests carried out to investigate the hydrodynamics of marine current turbines are presented. The objective is to build an experimental database in order to validate the numerical developments conducted to characterise the flow perturbations induced by marine current turbines. For that purpose, we used a tri-bladed horizontal axis turbine. The work is dedicated to measuring the behaviour of the system and to characterising the wake generated by the turbine. The efficiency of the device i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 11 publications
13
99
0
3
Order By: Relevance
“…However, it was not our intention to create site specific turbulence in this study, but to generate a range of flows with different turbulence intensities and length scales in order to investigate the specific contribution turbulence has to performance and blade loads. It was shown that increasing the turbulence intensity reduced the mean thrust and power ( Figure 24), and is consistent with previous studies that found a 10% reduction in power and thrust with an increase in turbulence intensity from ~5-15% [13]. However, it was found that the opposite occurs for increasing length scales which resulted in the power and thrust increasing (Figure 25).…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, it was not our intention to create site specific turbulence in this study, but to generate a range of flows with different turbulence intensities and length scales in order to investigate the specific contribution turbulence has to performance and blade loads. It was shown that increasing the turbulence intensity reduced the mean thrust and power ( Figure 24), and is consistent with previous studies that found a 10% reduction in power and thrust with an increase in turbulence intensity from ~5-15% [13]. However, it was found that the opposite occurs for increasing length scales which resulted in the power and thrust increasing (Figure 25).…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Another measure of eddy size may now be defined as the injection length scale and calculated using equation 13.…”
Section: Dissipation and Injection Length Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements of simulation accuracy at high λ may be possible using newly developed transitional turbulent models that can account for this laminar-turbulent transition behaviour [19]. Over prediction of Cp at high λ may also occur as a result of blockage errors that were not accounted for in EFD results which could artificially increase EFD Cp [26], and may also occur due to differences in the turbulence intensity levels between the CFD models and EFD testing, as high turbulence intensity levels can delay stall [27], leading to increases in Cp especially at high λ [28], with no turbulence intensity measurements recorded during EFD testing to compare to CFD turbulence levels. Significantly both CFD models were able to accurately capture the effect of geometrical changes on maximum Cp, which was simulated to within 14.3% and 6.3% of EFD results for turbines A and B…”
Section: Validation Of Numerical Simulations With Experimental Fluid mentioning
confidence: 99%